The other side of tomorrow - Cho, Tina (HarperAlley, an imprint of HarperCollins Publishers, 2024)
"This poignant and moving graphic novel in verse captures the dangers and hope that come with fleeing North Korea and reaching for a brighter future through the lives of Yunho and Myunghee. From never knowing where they'll find their next meal to avoiding soldiers lurking at every corner, many North Koreans have learned that sticking around can be just as deadly as attempting to flee . . . almost. Both shy, resourceful Yunho and fierce, vibrant Myunghee know this. So when they each resolve to run away from the bleak futures they face, it's with the knowledge that they could be facing a fate worse than death. While Yunho hopes to reunite with his omma, who snuck across the border years ago, Myunghee is reaching for dreams that are bigger than anything the regime would allow her to have. The two are strangers to each other until a chance encounter unwittingly intertwines their fates and Myunghee saves Yunho's life. Kept together by their dreams for a brighter future, they face a road plagued by poisonous jungle snakes, corrupt soldiers, and the daily fear of discovery and imprisonment. But with every step toward freedom, there is also hope. Will it be enough for both of them to make it to safety without losing each other along the way?"--Amazon.com.